Subjective norm and perceived enjoyment among students in influencing the intention to use e-learning / Zuhal Hussein - Hussein, Zuhal (IAEME, 2018)
E-learning is well known as a platform for transferring knowledge in the most effective way in terms of cost saving and it can be accessed by people widely and simultaneously. Now in the era of the 4th Industrial Revolution, Malaysian universities of higher learning have no choice but to move towards digital learning and open learning such as Massive Open Online Courses (MOOC) in order to be competitive. However, the success of the e-learning program depends not only on technology readiness or world competitiveness but also on the intention of students to use it. In order for e-learning to be successfully accepted and adopted by students, this study examined two factors, subjective norm and perceived enjoyment, affecting students’ intention to use e-learning in their education. One hundred and thirty-three students were recruited in this quantitative study through purposive sampling at the Health Campus, Universiti Sains Malaysia. A questionnaire with 30 items was used as a tool for data collection using survey methods. Consent was obtained from a respondent before starting the survey. Results indicated that those two factors did influence student behavioural intention. The highest mean value was perceived enjoyment (4.1058), followed by subjective norm and social influence (4.0391). Subjective norm was found to be significant and having a positive relationship with behavioural intention, while perceived enjoyment was not significant. In conclusion, future research on the intention of students to use e-learning is always relevant. Society may provide students with an alternative source for judging e-learning.